Serological indication of exposure to foot-and-mouth disease virus in comprehensively surveyed traditionally managed small ruminant population of Gujarat plains and hills agro-climatic region of India - ROUT, MANORANJAN; PRUSTY, BIKASH RANJAN; KANANI, AMIT (The Indian Journal of Animal Sciences, 2017)
The present sero-epidemiological study was conducted in Gujarat plains and hills agro-climatic region of India during 2013–2014 to detect infection-specific antibodies against foot-and-mouth disease virus (FMDV) exposure in apparently healthy, unvaccinated, traditionally managed sheep and goat population across 26 districts of Gujarat state. Serum samples from 1,295 small ruminants (381 sheep and 914 goats) were collected and subjected to 3AB3 nonstructural protein (NSP) ELISA for detection of FMDV NSP antibodies (Abs); where 111 of 381 (29.13%) sheep and 201 of 914 (21.99%) goats were positive suggesting their previous exposure to FMDV. Although the animals were not vaccinated, representative numbers of serum samples from both species were also tested in liquid phase blocking ELISA to cross-check the protective antibody titre against all three serotypes in the trivalent vaccine that revealed null or zero 'herd immunity'. The results illustrate the circulation of FMDV in sheep and goats in the particular agro-climatic region of the country and vaccination in these animals needs to be followed to build up desired level of herd immunity against FMD.